Respons Masyarakat terhadap Posisi Madrasah dalam Sistem Pendidikan Nasional - Nunu Ahmad An-Nahidl (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2007)
The reposition of madrasah becomes public school according to the law number 20/2003 on national education system is assumed giving some serious implications, especially dealing with achieving idealism has to be reached by madrasah, which is developed based on vision and mission of madrasah as Islamic education institution. madrasah should be constantly opened to its internal values, personal, character, need, and also strengths, and weaknesses. because madrasah was historically developed from the previous Islamic education institution, i.e. pesantren. so, madrasah should keep on in vision and mission of pesantren, i.e. tafaqquh fiddin.